From Adolescence to Old Age: Continuity, Change, and Identity Across the Lifespan - Ndiangui, Peter (Research in Social Sciences and Technology- OpenED Network, 2026)
This qualitative study examines how enduring dispositions and adaptive change interact over more than five decades among former secondary school classmates who studied together in the early 1970s in their twenties and reconnected in the 2020s in their early seventies. Using a narrative-based design, data were collected through cross-validated conversations, including telephone interviews, text messages, WhatsApp group discussions, and virtual meetings. Guided by Ecological Systems Theory and life-course perspectives, the analysis explores how individual agency operates within nested ecological, cultural, and historical contexts to shape identity, generativity, and adaptation in later adulthood. Findings show that core traits such as intellectual curiosity, empathy, loyalty, creativity, and moral commitment persisted across decades, even as priorities shifted toward family, health, community engagement, and mentorship. Narrative reconstruction through collective and individual storytelling reinforced identity coherence, social connection, and self-understanding, revealing that knowing others often uncovers only the aspects of self they choose to disclose. The confidence to reveal deeper dimensions of the core self, strengthens with age. Echoing the Rip Van Winkle metaphor, participants awoke to a transformed world while maintaining enduring qualities. The study highlights the coexistence of personality continuity and adaptive transformation and demonstrates how early dispositions, ecological influences, and culturally grounded meaning-making collectively shape human development across the lifespan.